2020
DOI: 10.7600/jpfsm.9.223
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of injuries in Japanese male collegiate rugby union players

Abstract: To the best of our knowledge, most previous studies regarding the epidemiology of injuries in rugby union (rugby) players have focused on professional players. Therefore, data on injuries in collegiate rugby players in Japan is limited. The purpose of this study was to conduct a prospective injury survey of Japanese male collegiate rugby players over several years and to analyze the injuries that occurred during matches and training according to field position, type of injury, and mechanism of injury. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Forty-four articles did not describe any sports ISSs or ISGs, one did not report sports injury data, three had retrospective study designs, 11 described surveillance systems that had ceased operation or were not ongoing, and seven presented duplicated information. The search process identified 28 studies, including six English articles 23 24 25 26 27 28 and 22 Japanese articles 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 , that met the inclusion criteria. A flow diagram of the screening and selection process of the studies is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-four articles did not describe any sports ISSs or ISGs, one did not report sports injury data, three had retrospective study designs, 11 described surveillance systems that had ceased operation or were not ongoing, and seven presented duplicated information. The search process identified 28 studies, including six English articles 23 24 25 26 27 28 and 22 Japanese articles 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 , that met the inclusion criteria. A flow diagram of the screening and selection process of the studies is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 selected studies, five included methodological details of ISSs or ISGs developed and currently used among sports in Japan (Aim 1) 29 30 41 44 45 , whereas 23 employed and described details of ongoing ISSs or ISGs developed overseas (Aim 2) 23 24 25 26 27 28 31 32 33 34 35 36 37 38 39 40 42 43 46 47 48 49 50 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations